2016
DOI: 10.3102/0013189x16649960
|View full text |Cite
|
Sign up to set email alerts
|

A Multigrade, Multiyear Statewide Examination of Reading Achievement

Abstract: This brief examined the patterns of reading achievement using statewide data from all students (Grades 3–10) in multiple years to examine gaps based on student, school, and district characteristics. Results indicate reading achievement varied most between students within schools and that students’ prior achievement was the strongest predictor of current achievement. Achievement gaps were identified for males, Black students, students receiving meal subsidies, and schools with higher proportions of students rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Importantly, these researchers also found that in the United States, there were greater differences in opportunity to learn within schools than between schools and essentially half of the within-school relationship between SES and mathematics literacy could be attributed to differences in opportunities to learn, most likely in the form of differences in level of curriculum provided, access to more advanced classes, instructional quality and teacher expectations within and between schools. Adelson, Dickinson, and Cunningham (2016) similarly found that reading achievement varied more within schools than between schools when analyzing statewide data for Kentucky, also implicating differences within schools in opportunities to learn.…”
Section: Opportunity To Learnmentioning
confidence: 92%
“…Importantly, these researchers also found that in the United States, there were greater differences in opportunity to learn within schools than between schools and essentially half of the within-school relationship between SES and mathematics literacy could be attributed to differences in opportunities to learn, most likely in the form of differences in level of curriculum provided, access to more advanced classes, instructional quality and teacher expectations within and between schools. Adelson, Dickinson, and Cunningham (2016) similarly found that reading achievement varied more within schools than between schools when analyzing statewide data for Kentucky, also implicating differences within schools in opportunities to learn.…”
Section: Opportunity To Learnmentioning
confidence: 92%
“…Students with ID can be successful in reading instruction, exhibit educational behavior in the desired direction, and educators can support this process with effective strategies (Keefe & Copeland, 2011). Moreover, improved reading skill in early grades has been linked to positive reading skill in later grades (Adelson, Dickinson, & Cunningham, 2016), school attendance, grade point average, and college attendance (Lesnick, George, Smithgall, & Gwynne, 2010). Thus, it is necessary to investigate effective instructional methods used to teach reading comprehension skills to students with ID.…”
Section: The Study Purpose and Research Questionmentioning
confidence: 99%
“…Zihin yetersizliği olan öğrenciler okuma öğretiminde başarılı olabilirler, istendik yönde eğitimsel davranışlar sergileyebilirler ve eğitimciler de bu süreci etkili stratejilerle destekleyebilirler (Keefe & Copeland, 2011). Ayrıca, erken yaşlarda edinilen okuma becerisinin sonraki yıllardaki okuma becerisine (Adelson, Dickinson & Cunningham, 2016), okula devam durumuna, genel ortalamaya ve üniversite katılımına (Lesnick, Goerge, Smithgall & Gwynne, 2010) 2006) tarafından kapsamlı bir derlemede incelenmiş olmasıdır. Bu yüzden, bu çalışma 2006 yılından sonra yapılmış çalışmalar ile sınırlandırılmıştır.…”
Section: çAlışmanın Amacı Ve Araştırma Sorusuunclassified